A new lignanamide from the stems of Derris elliptica (Wall.) Benth with antimicrobial and anti‐inflammatory activities. (6th November 2022) - Trang, Bui Thi Thu; Huong, Phan Thi Thanh; Anh, Nguyen Tuan; Huong, Nguyen Thi; Linh, Nguyen Thi Thuc; Van Kiem, Phan; Nhiem, Nguyen Xuan
Abstract: A new lignanamide, named derristicine A (1 ), together with ten known compounds, dalbin (2 ), wistin (3 ), 3, 5‐dimethoxy‐4‐hydroxy‐1‐ O ‐ β ‐D‐glucopyranoside (4 ), 3, 4, 5‐trimethoxyphenyl‐1‐ O ‐(4′‐sulfo)‐ β ‐D‐glucopyranoside (5 ), vanillic acid glucosyl ester (6 ), (9 R )‐roseoside (7 ), (9 S )‐roseoside (8 ), pumilaside A (9 ), (8 R, 8′ R )‐secoisolariciresinol‐9‐ O ‐ β ‐D‐glucopyranoside (10 ), and (8 S, 8′ S )‐secoisolariciresinol‐9‐ O ‐ β ‐D‐glucopyranoside (11 ) were isolated from Derris elliptica (Wall.) Benth stems. Their chemical structures were determined by analysis of HR‐ESI‐MS, NMR spectral data, as well as comparison with previous reports. Compounds 2 ‐3, 5 ‐8, and 10 showed potential inhibitory effect on the growth of Candida albicans strain with a MIC value of 37.5 μM. Compounds weakly inhibited NO production in LPS activated RAW264.7 cells. Abstract :